1999
DOI: 10.1046/j.1460-9568.1999.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutathione levels in neurochemically identified fibre systems in the aged rat lumbar motor nuclei

Abstract: The spinal cord motor nuclei have been the focus of a number of investigations exploring neurodegenerative mechanisms, e.g. excitotoxicity mediated by glutamate and oxidative stress. Here, high-resolution quantitative post-embedding immunocytochemistry with antibodies to oxidized and reduced glutathione (GSH), an ubiquitously expressed scavenger of free radicals, was used to examine if GSH synthesis is upregulated pre- and/or postsynaptically in the lumbar motor nuclei of aged (30 month old) rats. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…We could not get any data for aged-related change in GAD65 or 76. However, there is a report that Glutathione (gamma-glutamylcysteinylglycine), a neuromodulator at glutamate receptors, levels were significantly increased in neurochemically identified fibre systems in the aged rat lumbar motor nuclei [40], suggesting that aging in the spinal cord motor nuclei is associated with an increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…We could not get any data for aged-related change in GAD65 or 76. However, there is a report that Glutathione (gamma-glutamylcysteinylglycine), a neuromodulator at glutamate receptors, levels were significantly increased in neurochemically identified fibre systems in the aged rat lumbar motor nuclei [40], suggesting that aging in the spinal cord motor nuclei is associated with an increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we provide, for the first time, a 3‐D image of the intracellular distribution of GSH, by combining the specificity of polyclonal antibody labeling for GSH with the ability of confocal microscopy to provide sectional images from stained cells. This represents a development of the previously documented use of the antibody to assay GSH immunohistochemically (11, 12). Figure 1 details the staining pattern obtained by fluorescence microscopy of several cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the difficulties in using existing cytochemical methods to study intracellular GSH compartmentalization, we have explored the possibility of developing an immunocytochemical method, based on labeling fixed cell preparations with a GSH‐specific, polyclonal antibody that has hitherto been largely applied to histochemical analyzes (11, 12). Thus, in the present work, we report on the cellular localization of GSH in intact cells, using a combination of secondary fluorescence staining and confocal microscopy.…”
mentioning
confidence: 99%
“…As suggested by Edström et al (2007) the loss of synaptic input in terms of stripping of afferent boutons from spinal MNs seems to be highly selective and is associated with signs of neuroaxonal degeneration. An effect of reactive oxygen species have been implicated as axons and axon terminals with signs of neurodegeneration and/or neuroaxonal dystrophy have been observed to contain increased levels of total glutathione indicating redox stress (Ramirez‐Leon et al, 1999). Further, it has been suggested that axon impairment during aging may start as a distal process (cf.…”
Section: Neuromuscular Changes With Agingmentioning
confidence: 99%